A randomized clinical trial of oral versus intravenous methylprednisolone for relapse of MS. (May 2014) - Ramo-Tello, C; Grau-López, L; Tintoré, M; Rovira, A; Ramió i Torrenta, L; Brieva, L; Cano, A; Carmona, O; Saiz, A; Torres, F; Giner, P; Nos, C; et al.
Background: Steroids improve multiple sclerosis (MS) relapses but therapeutic window and dose, frequency and administration route remain uncertain. Objective: The objective of this paper is to compare the clinical and radiologic efficacy, tolerability and safety of intravenous methylprednisolone (ivMP) vs oral methylprednisolone (oMP), at equivalent high doses, for MS relapse. Methods: Forty-nine patients with moderate or severe relapse within the previous 15 days were randomized in a double-blind, noninferiority, multicenter trial to receive ivMP or oMP and their matching placebos. Expanded Disability Status Scale (EDSS) scores were determined at baseline and weeks 1, 4 and 12. Brain MRI were assessed at baseline and at weeks 1 and 4. Primary endpoint was a noninferiority assessment of EDSS improvement at four weeks (noninferiority margin of one point), with further key efficacy assessments of number and volume of T1 gadolinium-enhancing (Gd+), and new or enlarged T2 lesions at four weeks' post-treatment initiation. Secondary outcomes were safety and tolerability. Results: The study achieved the main outcome of noninferiority at four weeks for improved EDSS score. No differences were found between ivMP and oMP in the number of Gd+ lesions (0 (0–1) vs 0 (0–0.5), p = 0.630), volume of Gd+ lesions (0 (0–88.0) vs 0 (0–32.9) mm 3, p = 0.735), or new or enlarged T2 lesions (0 (0–194) vs 0 (0–123), p = 0.769). MP was well tolerated, and no serious adverse events were reported. Conclusions: This study provides confirmatory evidence that oMP is not inferior to ivMP in reducing EDSS, similar in MRI lesions at four weeks for MS relapses and is equally well tolerated and safe. Trial registration: clinicaltrials.gov identifier: NCT00753792